Associations between physical activity, sedentary behavior, and health risk behaviors among adolescents from a city in Southern Brazil - Michael Pereira da Silva; Fabio Eduardo Fontana; Gregory J. Welk; Pedro F. Saint-Maurice; Edmar Roberto Fantineli; Eliane Denise Araújo Bacil; Wagner de Campos (Revista Brasileira de Atividade Física e Saúde)
This study examined the independent and combined associations of physical activity (PA) and sedentary behavior (SB) with health risk behaviors in Brazilian adolescents. Participants were 893 adolescents (454 girls) from Curitiba, Brazil. The Youth Activity Profile questionnaire evaluated PA and the Adolescent Sedentary Questionnaire evaluated SB. The Youth Risk Behavior Surveillance System (YRBS) questionnaire evaluated fruit, vegetable, alcohol, and tobacco consumption. Binary Logistic regression measured the independent and combined associations of PA and SB with risk behaviors. PA was inversely associated with low fruit (OR = 0.30; 95%CI: 0.18-0.51) and vegetable consumption (OR = 0.43; 95%CI: 0.25-0.73), and tobacco use (OR = 0.52; 95%CI: 0.29-0.89). However, PA was positively associated with mild (OR = 1.54; 95%CI: 1.08-2.19) and excessive alcohol use (OR = 1.53; 95%CI: 1.01-2.33). Higher levels of PA were associated with reduced risks of smoking and healthier eating patterns, but higher likelihood of alcohol consumption.